2016
DOI: 10.1080/00365521.2016.1183705
|View full text |Cite
|
Sign up to set email alerts
|

Protein induced by vitamin K absence or antagonist-II (PIVKA-II) specifically increased in Italian hepatocellular carcinoma patients

Abstract: The combination of the two biomarkers, evaluated by the ROC analysis, improved the specificity compared to a single marker. These data suggest that the combined analysis of the two markers could be a useful tool in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…The results showed that combination of PIVKA-II and AFP further increase the efficiency for diagnosis of HBV related early stage HCC. This result was also in consistent with a few other studies using combination of the two markers as diagnostic marker of HCC [ 14 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results showed that combination of PIVKA-II and AFP further increase the efficiency for diagnosis of HBV related early stage HCC. This result was also in consistent with a few other studies using combination of the two markers as diagnostic marker of HCC [ 14 ].…”
Section: Discussionsupporting
confidence: 93%
“…Although PIVKA-II is mainly used as a diagnostic marker in Asia, studies in other populations, including Middle Eastern and European subjects, have also demonstrated its diagnostic value for HCC [ 11 13 ]. There has also been report that combination of PIVKA-II with other biomarkers may further increase the sensitivity and specificity for early diagnosis of HCC [ 14 ]. The PIVKA-II level has also recently drawn interest as a prognostic marker for HCC patients [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prothrombin induced by vitamin K absence II and CEA serum concentrations were determined on a Lumipulse G1200 (Fujirebio-Europe, Gent, Belgium), using the LUMIPULSE G PIVKA-II kit and the LUMIPULSE G CEA kit (Fujirebio, Tokyo, Japan) respectively ( 17 ). Lumipulse G1200 is a fully automated assay system for the quantitative measurement in serum specimen based on chemiluminescent enzyme immunoassay (CLEIA) technology by a two-step sandwich in immunoreaction cartridges.…”
Section: Methodsmentioning
confidence: 99%
“…However, owing to its low sensitivity and specificity, AFP testing alone is not recommended in diagnostic assessments of HCC [ 3 – 10 ]. Instead, it is used to combine with other serum or plasma tumor markers, which have been shown to have superior diagnostic abilities [ 3 , 6 , 11 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The role of DCP as a biomarker of HCC was first reported in a study published 1984 [ 17 ], which found that DCP was present in 91% of HCC patients but not detectable in other benign liver diseases. Subsequently, numerous studies [ 6 8 , 13 , 18 20 ] demonstrated that a combined analysis of DCP and AFP led to better prediction of HCC although there are some controversies about the diagnostic accuracy of DCP + AFP.…”
Section: Introductionmentioning
confidence: 99%